Smart Sukuk structure from Shari’ah perspective: the application of Mudarabah smart contract - Adam Sa'ad, Auwal (International Research Centre of Islamic Economics and Finance (IRCIEF), 2018)
Smart Sukuk structure is one of the most recent and significant structures for future sukuk issuances. In the era of crowed funding and Financial Technology Enhancement, the Smart Sukuk seems to be the future of Islamic fundraising for infrastructure and Business developments. The equity wise Mudarabah contract of the Islamic Finance has proved to be one of the most feasible contracts to govern the smart sukuk issuances. The conventional Mudarabah Sukuk structure represents projects or business activities managed based on Mudarabah contract. However, the unique features of smart sukuk and the proposed Mudarabah smart contract is that, it has given rooms for more players to participate in sukuk issuances, where as the conventional sukuk issuances has technically allowed mostly the participations of big players such as government agencies, banks and large companies among others. The revolutionary smart sukuk uses the block chain technology to boost the efficiency and makes the process more transparent and reduces the issuance cost to secure the involvements of small and medium enterprises SMEs, associations and social impact projects owners to participate in the sukuk issuances. The paper studied the structure of the conventional Mudarabah sukuk and proposed the newly smart Sukuk with its unique and innovative features structured under the concept of Mudarabah smart contract.